Drainage of the hepatic cyst by laparoscopy - clinical case - Falcón-Cancino, Luis A.; Baltazar-Herrera, Ernesto; Flores-López, Alejandro A.; Yépez-Vallejo, Segundo; Echevarría-Fernández, Fidel; Padrón-Arredondo, Guillermo; Villalobos-Rodríguez, Alejandro L. (International Journal of Research in Medical Sciences, 2023)
Liver cysts are formations of serous content surrounded by normal liver parenchyma, without communication with the bile duct. The cyst wall is generally lined with cuboidal epithelium surrounded by layers of connective tissue. They are rare entities in adult patients, generally, they are asymptomatic in 3%, and between 10-15% of all patients will generate symptoms that lead them to consult. A 38-year-old man with an external abdominal tomography study that reported a giant hepatic cyst. Laboratory blood tests: hemoglobin 7.9 g/dl; leukocytosis 11,000/ul; serum electrolytes, liver transaminases, and bilirubin were normal, alkaline phosphatase, and gamma glutamyl-transpeptidase 94 U/l and 241 U/l, respectively. Non-reactive anti-human immuno-deficiency virus (HIV 1) and two antibodies, venereal disease research laboratory (VDRL), cancer antigen (CA) 19-9 antigen, hepatitis B-C surface antigen, and carcinoembryonic antigen were negative. He underwent surgery by laparoscopic drainage of the liver cyst, through a median infraumbilical incision with the Hasson technique and placement of three 12 mm trocars, hepatomegaly was observed without finding an exit site for purulent material, it was punctured through liver segment V, and 2000 ml of citrine fluid was extracted. The hepatic wound is addressed with a 1-0 caliber chromic catgut thread, placing a Penrose-type drain. At 48 hours postoperatively, it evolves favorably, so it is decided to discharge. Hepatic cysts are fluid-filled cavities lined by a single-layered cuboidal or columnar biliary epithelium in the liver. A majority of hepatic cysts are found incidentally on liver imaging, such as abdominal ultrasonography, computed tomography, or magnetic resonance imaging.